System-Level Factors Contributing to Burnout and Professional Well-Being Among Transgender and Gender-Diverse Nurses - Hyunmin Yu; Celsea Tibbitt; J. Margo Brooks Carthon; Karen B. Lasater; José A. Bauermeister; Matthew D. McHugh (Health Equity)
Introduction: Transgender and gender-diverse (TGD) health care professionals face significant burnout, yet evidence on system-level factors such as workplace discrimination that contribute to this issue among TGD nurses is limited. Responding to the U.S. Department of Health and Human Services’ call for research on burnout among health care staff from diverse demographic backgrounds, this study aimed to examine the system-level factors affecting burnout and professional well-being among TGD nurses and identify strategies to enhance their well-being. Methods: This qualitative descriptive study employed directed content analysis of responses of 6 different open-text survey questions from 66 TGD nurses, utilizing 2 nurse survey datasets collected pre-pandemic (December 2019–February 2020) and during the pandemic (April 2021–June 2021). To identify the system-level factors influencing burnout and well-being, the themes were developed using both inductive and deductive analytic approaches, guided by the Systems Model of Clinical Burnout and Professional Well-being. Results: Three themes related to the system-level factors affecting burnout and professional well-being among TGD nurses were: (1) poor working conditions characterized by inadequate staffing and insufficient protective measures, (2) lack of leadership support and a non-inclusive culture highlighted by unsupportive leadership and workplace discrimination, and (3) non-patient-centered U.S. health care and LGBTQ+ stigma that create barriers to providing quality care for marginalized groups and receiving care for themselves. Recommendations from participants to enhance their professional well-being are also presented. Conclusion: To support the well-being of TGD nurses and improve the quality of care for all patients, health care organizations should implement system-level changes that create a physically and psychologically safe and inclusive work environment.